Age at diagnosis of autism spectrum disorders: is there an association with socioeconomic status and family self-education about autism? - Hrdlicka M (Dove Medical Press, 2016)
Michal Hrdlicka,1 Maria Vacova,1 Hana Oslejskova,2 Veronika Gondzova,2 Iveta Vadlejchova,3 Jana Kocourkova,1 Jiri Koutek,1 Iva Dudova1 1Department of Child Psychiatry, Charles University Second Faculty of Medicine and University Hospital Motol, Prague, 2Department of Child Neurology, Masaryk University Faculty of Medicine and University Hospital, Brno, 3Child Psychiatry Clinic, Chomutov, Czech Republic Background: The marked increase in autism spectrum disorders (ASD) prevalence has stimulated worldwide interest in exploring broader circumstances of care of autistic children, including the role of socioeconomic status (SES) and family information on autism.Methods: Our sample comprised of 160 children who participated in a diagnostic examination focused on autism, and their parents who completed a simple descriptive questionnaire focusing on the family situation as well as family self-education about autism. The diagnosis of ASD was confirmed in 120 children (75% of the sample; 94 boys, 26 girls) with mean age 6.2±2.7 years (median 5.3, range 2.2–17.2 years). In 71 autistic patients (59.2%), a diagnosis of mental retardation was also established.Results: The age at diagnosis of ASD correlated negatively with maternal (P=0.014) and paternal (P=0.002) ages at the time of birth of the ASD child as well as with paternal (P=0.002) and maternal (P=0.050) education. The age at diagnosis of ASD did not correlate with family SES. Mothers were significantly more active in seeking information on autism than fathers or both parents equally (80 vs 9 vs 28 cases, respectively; P<0.001). The mean number of information sources on autism was 3.5±1.8 with a range 0–9. The mean number of resources did not differ among the three SES groups (3.50 vs 3.49 vs 4.25, respectively; P=0.704). The mean number of sources did not correlate with the age at diagnosis of ASD. The most often used sources were the Internet (81.7%), followed by psychologists (48.3%), books (46.7%), and child and adolescent psychiatrists (43.3%).Conclusion: An earlier diagnosis of ASD is associated with higher parental age at birth and higher parental education but not with family SES or number of family information sources. Keywords: autism spectrum disorders, early diagnosis, socioeconomic status, parental education, parental information